Common Problems of Adolescents Encountered in Schools - McWhinney, Betty D. (1986)
Some adolescents present in school with problems of poor academic performance and unacceptable behaviour. A physician's evaluation of such a problem requires a careful history and consideration of emotional factors. A neuro-developmental assessment should reveal a pattern of strengths as well as any areas of delay. Management includes demystifying the problem to the student and counselling parents, as well as providing an explanation to the school staff. Stimulant medication, when the primary problem is one of attention-deficit disorder, can be a useful part of the therapeutic program. Long-term follow up, counselling and support are essential. Working within the school gives the counsellor access to teachers and other staff to ensure that understanding of, and help with, the problem continues.